A Reforma do Bolsa Família : Avaliação das Propostas de Reforma Debatidas em 2019 - Morgandi, Matteo (Washington, DC : World Bank, 2022)
As part of the ongoing debate on the modernization of the Bolsa Familia (BF) program, several reform proposals were presented through 2019, including by the Ministry of Citizenship (MoC), Congress and the think tank IPEA, the latter as part of a broader proposal to consolidate various expenditures. This note uses the BraSIM microsimulation model to evaluate the 2019 proposals in the context of Brazil’s tax benefit system. All proposals lead to a higher number of beneficiaries, with the poorest families, especially children and youth, benefitting the most. In general, the progressive incidence of the current program would vary little in the MoC and Congress reforms, but is reduced in IPEA’s, which includes a universal component. The three proposals have different contributions on poverty-reduction: IPEA’s reform is significantly less efficient than the current scenario and other reforms in terms of cost-effectiveness. However, IPEA’s proposal most contributes to the reduction of inequality, and is the only one that identifies financing sources through the extinction of more regressive expenditures. Through this comparative analysis, the Note also highlights the main dilemmas about the future of the program, which remain relevant even in the post-COVID-19 reality: the tension between generosity and coverage; the priorization of certain groups for poverty-reduction; reconciling the program's objective of encouraging human capital for children with its role of minimum income guarantee; the risks of eliminating a “basic benefit”. While only IPEA’s proposal identified financing sources for the program’s expansion, the Note reveals additional potential sources of financing for the BF program in the tax benefit system.